Aggregation and contingent metal/surface reactivity of 1,3,8,10-tetraazaperopyrene (TAPP) on Cu(111) - Matena, Manfred; Stöhr, Meike; Riehm, Till; Björk, Jonas; Martens-Kruck, Susanne; Dyer, Matthew S.; Persson, Mats; Lobo-Checa, Jorge; Müller, Kathrin; Enache, Mihaela; Wadepohl, Hubert; Zegenhagen, Jörg; et al. (Chemistry - a European journal, 2010)
The structural chemistry and reactivity of 1,3,8,10-tetraazaperopyrene (TAPP) on Cu(111) under ultra-high-vacuum (UHV) conditions has been studied by a combination of experimental techniques (scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy, XPS) and DFT calculations. Depending on the deposition conditions, TAPP forms three main assemblies, which result from initial submonolayer coverages based on different intermolecular interactions: a close-packed assembly similar to a projection of the bulk structure of TAPP, in which the molecules interact mainly through van der Waals (vDW) forces and weak hydrogen bonds; a porous copper surface coordination network; and covalently linked molecular chains. The Cu substrate is of crucial importance in determining the structures of the aggregates and available reaction channels on the surface, both in the formation of the porous network for which it provides the Cu atoms for surface metal coordination and in the covalent coupling of the TAPP molecules at elevated temperature. Apart from their role in the kinetics of surface transformations, the available metal adatoms may also profoundly influence the thermodynamics of transformations by coordination to the reaction product, as shown in this work for the case of the Cu-decorated covalent poly(TAPPCu) chains.
Gesehen am 25.05.2023